2002
DOI: 10.1023/a:1014809607758
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Gamma glutamyltransferase (GGT) is a plasma membrane bound enzyme that initiates the degradation of glutathione. The presence of several promoters in the rat GGT gene indicates strict control and regulation of its expression. The aim of this study was to investigate whether the GGT gene was regulated differently after butyrate-induced differentiation and oxidative stress exposure of rat colon carcinoma cells and whether the regulation was related to the glutathione level. The activity of GGT was upregulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A further use of the probe has been demonstrated by monitoring intracellular GGT level regulated by NaBu (a potential anticancer drug). As is known, NaBu has multiple effects on cell growth, differentiation and apoptosis, and thus its potential use is of great interest. On the other hand, several GGT overexpressed cancer cells, such as melanoma, ovarian cancer cells, breast cancer cells (MCF-7), and colon carcinoma cells, could further upregulate the level of GGT after treatment with NaBu. In consideration of the excellent performance of CV-Glu for visualizing GGT in living cells, we intend to explore the relationship between the GGT expression level and NaBu stimulation in HepG2 cells by using fluorescence imaging method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further use of the probe has been demonstrated by monitoring intracellular GGT level regulated by NaBu (a potential anticancer drug). As is known, NaBu has multiple effects on cell growth, differentiation and apoptosis, and thus its potential use is of great interest. On the other hand, several GGT overexpressed cancer cells, such as melanoma, ovarian cancer cells, breast cancer cells (MCF-7), and colon carcinoma cells, could further upregulate the level of GGT after treatment with NaBu. In consideration of the excellent performance of CV-Glu for visualizing GGT in living cells, we intend to explore the relationship between the GGT expression level and NaBu stimulation in HepG2 cells by using fluorescence imaging method.…”
Section: Resultsmentioning
confidence: 99%
“…[30][31][32][33][34] On the other hand, several GGT overexpressed cancer cells, such as melanoma, ovarian cancer cells, breast cancer cells (MCF-7) and colon carcinoma cells, could further upregulate the level of GGT after treatment with NaBu. [35][36][37] In consideration of the excellent performance of CV-Glu for visualizing GGT in living cells, we intend to explore the relationship between GGT expression level and NaBu stimulation in HepG2 cells by using fluorescence imaging method. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Prior to such an attempt, the influence of NaBu on both the fluorescence of CV-Glu and the activity of GGT was first examined.…”
Section: Monitoring Of Intracellular Ggt Level Regulated By Nabumentioning
confidence: 99%
“…A time- and dose-dependent increase in GGT mRNA and GGT activity was reported in CC531 rat colon carcinoma cells exposed to ionizing radiation, which caused the formation of reactive oxygen and nitrogen species (Pankiv, Moller, Bjorkoy, Moens, & Huseby, 2006). In the same cell line, menadione treatment induced both ROS and GGT activity (Mikkelsen, Mortensen, Laperche, & Huseby, 2002). In a subsequent study, the authors reported that ROS induced GGT involved activation of Ras and was mediated through an AKT, p38 MAPK and MEK1 dependent pathway (Pandur, Pankiv, Johannessen, Moens, & Huseby, 2007).…”
Section: Redox Regulation Of Ggtmentioning
confidence: 99%